2013
DOI: 10.1002/ajmg.a.36278
|View full text |Cite
|
Sign up to set email alerts
|

Partial trisomy 1q41‐qter and partial trisomy 9pter‐9q21.32 in a newborn infant: An array CGH analysis and review

Abstract: We report on a girl who presented with distinctive abducted hip and hyperextended knee. Cytogenetic analysis detected an extra derivative chromosome resulting from a balanced translocation in the mother and 3:1 segregation. Using array comparative genomic hybridization (CGH) in combination with conventional high resolution GTG banding, we designate the karyotype as 47, XX, +der(9)t(1;9)(q41;q21.32)mat, indicating tertiary trisomy of chromosome segments 1q41-qter and 9pter-9q21.32. A review and genotype-phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Many genetic disorders and cancers in humans are associated with segmental duplication 6 7 10 11 12 13 14 17 19 . However, the relationship between these specific segmental duplications and their phenotypic consequences are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many genetic disorders and cancers in humans are associated with segmental duplication 6 7 10 11 12 13 14 17 19 . However, the relationship between these specific segmental duplications and their phenotypic consequences are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-throughput genome analysis can detect chromosome copy number variation including segmental aneuploidy, it cannot distinguish among types of segmental duplication, such as tandem duplications, duplications inserted into an independent chromosome or generation of independent chromosome. Segmental duplications involving large chromosomal regions are associated with both adverse and beneficial effects in different organisms 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 and result from various types of spontaneous chromosomal mutation, such as tandem intra-chromosomal duplication, inter-chromosomal duplication by translocation, supernumerary chromosomes (structurally abnormal extra chromosomes) and episomal (ring) chromosomes 23 . In this report, we use the term “segmental duplication” to refer to amplification of a particular chromosomal region and “segmental aneuploidy” to refer to a duplication in which the chromosomal region is present as an independent chromosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five additional cases of carrier mothers of chromosomal rearrangements in 9q21‐22 with an estimate of 23% risk of unbalanced products by a 3:1 segregation pattern exist. This risk and segregation pattern can be applied to our case because the second pregnancy was also affected by partial trisomy 9 .…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated in Table 1, as in 5 out of 9 cases with pure 1q trisomy, this region is implicated [8,11,13,20]. Furthermore, recently a new case of trisomy 1q41-qter has been described in a patient who also has a partial trisomy 9pter-9q21.32, derived from a 3:1 segregation of a maternal balanced translocation, and it has been suggested that the break-point is associated with the presence of a fragile site (FRA1H) localized to 1q41-q42.1 [38]. The chromosomal analysis of our family revealed 4 female carriers of the balanced translocation (Figure 1) and this has an important implication for genetic counseling.…”
Section: Discussionmentioning
confidence: 99%